Late caecal fistula after laparoscopic appendectomy managed mini-invasively – case report - Kwiatkowski, Andrzej (Termedia Publishing House, 2011)
Laparoscopic appendectomy is being performed increasingly, worldwide. The laparoscopic approach is associated with a lower complication rate and a shorter period of disability but some major complications still occur. We present a case of a 22-year-old woman who underwent laparoscopic appendectomy for acute appendicitis. In 3 weeks time after surgery, after physical activity the patient presented acute abdomen. Exploratory laparoscopy revealed peritonitis caused by caecal fistula. Laparoscopic lavage and drainage of the peritoneal cavity with formal caecostomy was performed. The postoperative course was uneventful. The stoma was closed in 6 months’ time without other complications. In our opinion laparoscopy is proven to be a safe and good option for diagnostics and treatment of some complications of appendectomy.